Enhancing School Effectiveness: The Impact of Principal Leadership, Infrastructure Utilization, and Administrative Services in Junior High Schools - Fita Ramadhani; Sugiyono Sugiyono; Resky Nuralisa Gunawan; Zafrullah Zafrullah (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study investigates the influence of principal leadership, infrastructure utilization, and administrative services on school effectiveness in public junior high schools in Tual City. Effective school management is essential for improving educational outcomes, particularly in regions where resources and leadership play a critical role in performance. The research involved 133 teachers and 318 students, selected through appropriate sampling techniques. Data were collected using a structured questionnaire covering four key variables: principal leadership, infrastructure use, administrative services, and school effectiveness. Data analysis was conducted using SPSS version 25, employing tests for normality, linearity, multicollinearity, and heteroscedasticity to ensure statistical validity. Findings revealed that principal leadership, infrastructure use, and administrative services were rated in the high category, with more than 86% of both teacher and student responses reflecting positive perceptions. Regression analysis showed a positive and significant combined effect of these three variables on school effectiveness, with results for teacher responses (F = 5.122, sig. = 0.00) and student responses (F = 32.334, sig. = 0.00) indicating strong statistical significance. These results emphasize the crucial role of leadership quality, efficient use of infrastructure, and strong administrative support in enhancing school effectiveness. The study underscores the need for targeted efforts in strengthening these areas to improve the overall quality of education in Tual City's junior high schools.